2019
DOI: 10.3390/atmos10100570
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of NMC and Ensemble-Based Climatological Background-Error Covariances in an Operational Limited-Area Data Assimilation System

Abstract: The evaluation of several climatological background-error covariance matrix (defined as the B matrix) estimation methods was performed using the ALADIN limited-area modeling data-assimilation system at a 4 km horizontal grid spacing. The B matrices compared were derived using the standard National Meteorological Center (NMC) and ensemble-based estimation methods. To test the influence of lateral boundary condition (LBC) perturbations on the characteristics of ensemble-based B matrix, two ensemble prediction sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…EXP_CV5 and EXP_CV7 assimilate radar observations (both reflectivity and radial velocity) every 3 h from 0600 UTC to 1200 UTC, taking the analysis field assimilated at 1200 UTC as the initial field and integrating forward for 6 h. The difference is that the former uses the BE matrix of the CV5 scheme for assimilation, while the latter uses the BE matrix of the CV7 scheme for assimilation. Current studies generally agree that the BE matrix obtained statistically using the NMC method overestimates the characteristic length scale (Liu et al, 2005;Li et al, 2012;Sun et al, 2016;Stanesic et al, 2019;Thiruvengadam et al, 2020). Therefore, in the two assimilation experiments, the length scales are reduced to half of the default value, which are set to 0.5.…”
Section: Model Configuration and Experimental Designmentioning
confidence: 86%
“…EXP_CV5 and EXP_CV7 assimilate radar observations (both reflectivity and radial velocity) every 3 h from 0600 UTC to 1200 UTC, taking the analysis field assimilated at 1200 UTC as the initial field and integrating forward for 6 h. The difference is that the former uses the BE matrix of the CV5 scheme for assimilation, while the latter uses the BE matrix of the CV7 scheme for assimilation. Current studies generally agree that the BE matrix obtained statistically using the NMC method overestimates the characteristic length scale (Liu et al, 2005;Li et al, 2012;Sun et al, 2016;Stanesic et al, 2019;Thiruvengadam et al, 2020). Therefore, in the two assimilation experiments, the length scales are reduced to half of the default value, which are set to 0.5.…”
Section: Model Configuration and Experimental Designmentioning
confidence: 86%
“…Numerous validation and verification methods, in both an operational and in a research context, applied over the years confirmed that the ALADIN model also provides very good representation of the vertical state of the atmosphere (e.g., Horvath et al, 2009;Ivančan-Picek et al, 2016;Stanešić et al, 2019). For ALADIN-HR44, the vertical grid is stretched with 73 hybrid sigma-pressure levels, with the lowest vertical level at approximately 10 m above ground level, while dynamic adaptation products have 15 vertical levels (with 8 levels in the first 1000 m).…”
Section: Numerical Modelmentioning
confidence: 97%
“…An alternative technique to calculate the static error statistics is the ensemble-based method (ENS) [45], where the forecast differences are the differences between two ensemble members, i.e., member i and member i + 1, where i denotes the sequence index of an ensemble member. Compared to the NMC method, the static error statistics from the ENS method have been demonstrated to improve the forecast quality [44,46]. Therefore, the ENS method was adopted to calculate the B-matrix in this study.…”
Section: Design Of Feature-dependent Bmentioning
confidence: 99%
“…Remote Sens. 2022, 14, 4537 6 of 22 method, the static error statistics from the ENS method have been demonstrated to improve the forecast quality [44,46]. Therefore, the ENS method was adopted to calculate the B-matrix in this study.…”
Section: Design Of Feature-dependent Bmentioning
confidence: 99%